Analisis Pembelajaran Berdiferensiasi Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial Kelas IV SD - Adelia, Shafira Iman; Fine Reffiane; Suyitno (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to analyze the application of differentiated learning in the subject of Natural and Social Sciences (IPAS) in grade 4 of SD Negeri 1 Penganten. The differentiated approach allows teachers to adjust the material, process, and learning products according to the diverse needs, interests, and abilities of students. A qualitative method with a case study approach was used in this study, involving observation, interviews with teachers and students, and analysis of learning documents. The results of the study indicate that differentiated learning can increase student engagement and understanding of the IPAS material, especially through the application of strategies and media that are tailored to individual learning styles. Teachers also show flexibility in using various approaches, such as giving different assignments, diverse learning groups, and utilizing technology in the learning process. However, the challenges faced include limited time and resources to implement differentiated learning optimally. Therefore, this study suggests the need for adequate training and provision of resources for teachers to strengthen the application of differentiated learning at the elementary school level.